2019
DOI: 10.1016/j.jviromet.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex real-time PCR assay for the detection and differentiation of the newly emerged porcine circovirus type 3 and continuously evolving type 2 strains in the United States

Abstract: A B S T R A C TA multiplex quantitative real-time polymerase chain reaction (mqPCR) assay was developed and validated for the detection and differentiation of porcine circovirus type 3 (PCV3) and type 2 (PCV2) strains. The assay coverage was 97.9% (184/188) for PCV3 and 99.1% (1889/1907) for PCV2 sequences that were available from the current GenBank database. The PCR amplification efficiencies were 98-99% for plasmids, and 92-96% for diagnostic samples, with correlation coefficients all greater than 0.99. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…However, those PCRs are designed for detection of a single viral agent at a time. Recently, duplex PCRs were developed for simultaneous detection of both PCV2 and PCV3 [26,27,28]. In the present study, we report the development and validation of a mPCR that allows simultaneous detection of these three important viruses in clinical samples.…”
Section: Introductionmentioning
confidence: 91%
“…However, those PCRs are designed for detection of a single viral agent at a time. Recently, duplex PCRs were developed for simultaneous detection of both PCV2 and PCV3 [26,27,28]. In the present study, we report the development and validation of a mPCR that allows simultaneous detection of these three important viruses in clinical samples.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, when single nucleotide mismatch in such situations is considered in the design of the primers and probes, strain coverage can potentially increase to 93.4 %–95.1 %. With that said, this genotyping assay should not replace general detection assays that may have higher strain coverage ( Wang et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…This simplified method is a low-cost and faster turnaround protocol, and should facilitate the genotyping process for field PCV2 strains. We have already developed a PCV2 general assay using the conserved ORF1 gene as the target ( Wang et al, 2019a ), which has enabled us to have a much higher strain coverage (99.1 %) for PCV2 detections. By utilizing that generic test for general detection and surveillance, followed by the genotyping PCR reported here, we should be able to detect and differentiate the majority of field PCV2 strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a more rapid and specific rLAMP assay using targetspecific fluorescence assimilating probes to facilitate real-time detection of PCV3 was successfully developed and was evaluated with clinical samples. To the best of our knowledge, the PCV3 rLAMP assay described herein is the first assimilating probe-applied LAMP assay used to diagnose PCV3 in real time; this method is more specific and reliable than the conventional LAMP assay that relies on non-target-specific monitoring methods (Park et al, 2018;Wang et al, 2019). As a result of the clinical evaluation, it was confirmed that the developed rLAMP has similar sensitivity and specificity to the previously reported qPCR for detection of PCV3 (Table 2 and each method has its unique pros and cons (Gadkar, Goldfarb, Gantt, & Tilley, 2018;Kouguchi, Fujiwara, Teramoto, & Kuramoto, 2010;Kubota et al, 2011;Kubota & Jenkins, 2015;Liu et al, 2017;Nyan & Swinson, 2015;Tanner, Zhang, & Evans, 2012;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%